Local Triamcinolone Treatment Affects Inflammatory Response in Seroma Exudate of Abdominoplasty Patients: A Randomized Controlled Trial. Issue 2 (25th January 2021) - Anker, Alexandra M.; Felthaus, Oliver; Prantl, Lukas; Geis, Sebastian; Brébant, Vanessa; Kehrer, Andreas; Strauss, Catharina; Ruewe, Marc; Vykoukal, Jody; Klein, Silvan M.
Abstract : Background: As the leading complication of abdominoplasty, seroma formation might represent an inflammatory process in response to surgical trauma. This prospective randomized trial investigated whether local administration of the antiinflammatory agent triamcinolone could prevent seroma accumulation. Methods: Weekly and cumulative seroma volumes were compared between the study groups A, B, and C over a 4-week follow-up (group A, with drain, without triamcinolone; group B, without drain, without triamcinolone; group C, without drain, with triamcinolone). Aspirated seroma samples were analyzed by enzyme-linked immunosorbent assay for selective inflammatory mediators. Results: Triamcinolone significantly reduced cumulative seroma volume (n = 60; mA 845 ± SDA 578 ml, mC 236 ± SDC 381 ml, p = 0.001). The most accentuated suppressive effect of triamcinolone was observed shortly after the treatment (week 1) (mA1 616 ± SDA1 457 ml, mB1 153 ± SDB1 161 ml, mC1 22 ± SDC1 44 ml, p A1/C1 < 0.001, p B1/C1 = 0.014). Local triamcinolone administration resulted in a differential concentration of interleukin-6 (IL-6) and matrix metalloproteinase-9 (MMP-9 (week 1) in seroma exudate as measured by enzyme-linked immunosorbent assay (mIL-6A1 1239 ± SDA1 59 pg/ml, mIL-6C1 848 ± SDC1 80 pg/ml, p < 0.001; mMMP-9A1 2343 ± SDA1 484 pg/ml, mMMP-9C1 376 ± SDC1 120 pg/ml, p = 0.001). Conclusions: Local administration of 80 mg of triamcinolone reduced postabdominoplasty seroma accumulation significantly. Under triamcinolone treatment, suppressed levels of IL-6 and MMP-9 in seroma fluid were observed. Notably, inflammatory marker suppression correlated clinically with a decrease in seroma accumulation. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.